Anesthetic management of a pediatric patient with situs solitus and dextrocardia (Indian Journal of Case Reports, 2024)
Dextrocardia with situs inversus is a rare heart condition with a genetic predisposition. Although most individuals lead a normal healthy life and usually, it is an incidental finding. Due to their unique anatomical variations and associated congenital variations, they may pose challenges to attending clinicians. We are hereby reporting a successful anesthetic management of the case of a 2.5-year-old child who presented for emergency laparotomy and on investigations, was found to have dextrocardia along with situs solitus.